2‐(2‐Nitrovinyl)furan Promotes Oxidation of Cellular Proteins, Lipids, and DNA of Male Rat Liver and Kidney. Issue 3 (11th November 2014) - Ajiboye, T. O.; Alabi, K. A.; Ariyo, F. A.; Adeleye, A. O.; Ojewuyi, O. B.; Balogun, A.; Sunmonu, T. O.
ABSTRACT: The effect of 2‐(2‐nitrovinyl)furan on the redox status of male rat liver and kidney was evaluated. Twenty male rats were randomized into four groups; group A received olive oil and groups B, C, and D rats received 12.5, 25, and 50 mg/kg bodyweight of 2‐(2‐nitrovinyl)furan intraperitoneally, daily at 24 h interval, respectively, for 14 days. 2‐(2‐Nitrovinyl)furan significantly reduced ( P < 0.05) alkaline phosphatase, alanine, and aspartate aminotransferase activities in male rat liver and kidney with a corresponding increase in serum. The activities of superoxide dismutase, catalase, glutathione peroxidase, glutathione reductase, and levels of reduced glutathione/glutathione disulfide (GSSG) ratio in the liver and kidney of 2‐(2‐nitrovinyl)furan‐treated rats decreased significantly ( P < 0.05). In contrast, GSSG, protein carbonyl, conjugated dienes, lipid hydroperoxides, malondialdehyde, and fragmented DNA (%) in 2‐(2‐nitrovinyl)furan‐treated rats increased significantly ( P < 0.05). Overall, data from this study revealed that 2‐(2‐nitrovinyl)furan exhibited its toxic effect by suppressing or depleting the antioxidant systems.